Colchicine Blocks Tubulin Heterodimer Recycling by Tubulin Cofactors TBCA, TBCB, and TBCE - Nolasco, Sofia; Bellido, Javier; Serna, Marina; Carmona, Bruno; Soares, Helena; Zabala, Juan Carlos (Frontiers in Cell and Developmental Biology, 2021)
Colchicine has been used to treat gout and, more recently, to effectively prevents autoinflammatory diseases and both primary and recurrent episodes of pericarditis. The anti-inflammatory action of colchicine seems to result from irreversible inhibition of tubulin polymerization and microtubule (MT) assembly by binding to the tubulin heterodimer, avoiding the signal transduction required to the activation of the entire NLRP3 inflammasome. Emerging results are showing that the MT network is a potential regulator of cardiac mechanics. Here, we investigated how colchicine impacts in tubulin folding cofactors TBCA, TBCB and TBCE activities. We show that TBCA is abundant in mouse heart insoluble protein extracts. Also, a decrease of the TBCA/β-tubulin complex followed by an increase of free TBCA is observed in human cells treated with colchicine. The presence of free TBCA is not observed in cells treated with other anti-mitotic agents as nocodazole or cold shock, or even after translation inhibition by cycloheximide. In vitro assays show that colchicine inhibits tubulin heterodimer dissociation by TBCE/TBCB, probably by interfering with interactions of TBCE with tubulin dimers, leading to free TBCA. Depletion of TBCA by RNAi, as well as overexpression cause the decrease of tubulin heterodimers levels. Together, these data strongly suggest that TBCA is mainly receiving β-tubulin from the dissociation of pre-existing heterodimers instead of newly synthesized tubulins. The TBCE/TBCB+TBCA system is crucial for controlling the critical concentration of free tubulin heterodimers and MT dynamics in the cells by recycling the tubulin heterodimers. It is conceivable that colchicine affects tubulin heterodimer recycling through the TBCE/TBCB+TBCA system producing the known benefits in the treatment of pericardium inflammation.